Proposed Marketing Strategy For Dapur Iga Resto and Cafe In Burangrang At PT. Dapur Iga Nusantara (The Indonesian Journal of Business Administration, 2014)
Abstract. Culinary business is a very promising business in Bandung city. This is due to the growth of the Indonesian population is increasing every year and is also accompanied by good economic growth in Bandung. Dapur Iga is one of the restaurants engaged in the industry. In the midst of the culinary industry competition is very tight, Dapur Iga already has a good sales performance, but still has not been able to reach their targets. Dapur Iga is under the trademark name of PT. Dapur Iga Nusantara which offers food products such as beef ribs as a main product that target young adults who have the economic status of B+. To be able to help and resolve the business issues, the formulation of such a strategy is needed to analyze the internal environment of Dapur Iga and external environment such as a competitor, the culinary industry analysis, etc. The data collected comes from primary and secondary data. The results of the environmental analysis are the strengths, weaknesses, opportunities and threats (SWOT) of Dapur Iga. SWOT analysis is the basis for making business or marketing strategy and to identify the root cause problem. After getting the SWOT analysis and the root cause, next is to make a solution of the weaknesses and threats by empowering the strength and opportunities of Dapur Iga. The solution is created based on the root cause analysis using fishbone diagram and categorized by the 7Pâ€™s of marketing mix as the solution.The last thing to be done is the implementation or carrying out the activities of the business solution by calculating budget and scheduling activities with timeline. By performing the solution that already formulated, expected Dapur Iga will solve their business issue. Therefore Dapur Iga has a good potential to grow and compete in the culinary industry in Indonesia, especially in Bandung.Â Keyword: Dapur iga, Marketing Strategy, Culinary Industry, Creative Economic, Business Strategy.